Autologous Fat Grafting Restores Soft-tissue Contour Deformities after Vascular Anomaly Surgery. Issue 5 (May 2019) - Teresa Minjung, O; Chan, Kimberly; Brennan, Tara; Roden, Dylan; Shamouelian, David; Chung, Ho Yun; Waner, Milton
Abstract : Background: Soft-tissue loss is expected after resection of large vascular lesions. Autologous fat transfer improves asymmetries; however, systematic outcomes are not previously described for vascular anomaly reconstruction. Methods: Retrospective chart review from 2012 to 2015 included patients receiving autologous fat transfers for soft-tissue defects during or following vascular anomaly surgery at a tertiary care center. Patients received dermal en bloc fat grafts, lipoaspirates, or both. Pre- and postoperative photographs were blindly reviewed by 3 facial plastic surgeons using a 5-point scale. Dermal abdominal en bloc fat grafts were placed immediately after excision of a vascular anomaly. Lipoaspirate fat grafting was performed using liposuction (modified Coleman technique) and centrifugation. The effectiveness of fat transfers was assessed using patients' photographs. Final follow-up was 6 months to 5 years. Results: There were 35 autologous fat transfer surgeries in 27 patients. Fourteen patients received en bloc dermal fat grafts (14 total), 13 lipoaspirate transfers (21 total), and 3 both. Ages ranged from 2 to 69 years (mean = 25 years). Majority of patients (81%) had head and neck lesions. Average volume of fat injected was 16.5 mL (range 0.8–100 mL). The average observer rating score was 2.45 [1–5 (5-point scale)] in the en bloc fat graft group versus 3.83 in the lipoaspirate group ( P < 0.0001) with acceptable inter-rater reliability between 3 observers (coefficient of concordance = 0.76). Follow-up ranged from 6 months to 5 years. There were 2 complications in the dermal fat graft group and none in the lipoaspirate group. Conclusions: Autologous fat transfer improves symmetry and scarring after surgical treatment of vascular anomalies. Fat grafting is permanent and reliable and creates a more symmetric soft-tissue contour compared with dermal fat grafts.